2014
DOI: 10.1007/s40141-014-0055-0
|View full text |Cite
|
Sign up to set email alerts
|

Driving After Traumatic Brain Injury: Evaluation and Rehabilitation Interventions

Abstract: The ability to return to driving is a common goal for individuals who have sustained a traumatic brain injury. However, specific and empirically validated guidelines for clinicians who make the return-to-drive decision are sparse. In this article, we attempt to integrate previous findings on driving after brain injury and detail the cognitive, motor, and sensory factors necessary for safe driving that may be affected by brain injury. Various forms of evaluation (both in clinic and behind-the-wheel) are discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…These include studies of measures of driving capacity [8,10,11], rates of traffic accidents [12][13][14], the predictive validity of neuropsychological [7,9] or functional tests for return to driving [4], and the impact of TBI-related cognitive impairment on driving outcomes [1][2][3]6,12]. This research has yielded complex and sometimes-contradictory findings, summarized in several literature reviews [1,6,7], but leaves little question that TBI-related deficits often affect driving adversely. Indeed, the association between TBI and driving problems commonly is assumed [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…These include studies of measures of driving capacity [8,10,11], rates of traffic accidents [12][13][14], the predictive validity of neuropsychological [7,9] or functional tests for return to driving [4], and the impact of TBI-related cognitive impairment on driving outcomes [1][2][3]6,12]. This research has yielded complex and sometimes-contradictory findings, summarized in several literature reviews [1,6,7], but leaves little question that TBI-related deficits often affect driving adversely. Indeed, the association between TBI and driving problems commonly is assumed [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…On-road Driving -The "Gold Standard" measure Whilst a variety of tests can be used to inform decisions about whether to revoke a driving licence Hird et al, 2014;Schultheis & Whipple, 2014), the primary decisionmaking tool remains in many cases the on-road driving test (Di Stefano & MacDonald, 2012;Dickerson, 2013;Ranchet et al, 2016;Ross et al, 2016). The advantages of real-world driving tests are fairly clear -the driver has to be able to demonstrate safe and appropriate behaviours when navigating real streets, interacting with other vehicles as well as vulnerable road users (Joanne M. Wood, Lacherez, & Tyrrell, 2014;Joanne M. Wood, Marszalek, Carberry, Lacherez, & Collins, 2015), and carry out a variety of tasks such as lane keeping and obeying traffic rules when driving at both fast (motorway) and slow (urban and parking) speeds.…”
Section: Testing Visual Function For Drivingmentioning
confidence: 99%
“…A recent survey of adult drivers found that those with a lifetime history of TBI have significantly higher odds of involvement in aggressive driving and serious MVAs within the previous 12 mo when compared to non-TBI drivers [9]. TBI can affect many areas of cognition necessary for safe driving, including planning, inhibition, attentional allocation, insight, memory, and information processing speed [10]. Moreover, TBI can result in physical symptoms (e.g., headaches, blurred vision, photophobia) that can challenge safe driving [11].…”
Section: Combat Veterans Of Iraq and Afghanistan (Operation Iraqi Frementioning
confidence: 99%